Letters from Julia and Avery Morgan to Cousin Lucy and Cousin Pierre Le Brun, November 14, 1898 - Julia Morgan::::::author:::; Avery Morgan::::::::: (1898)
On November 14th, 1898, Julia Morgan wrote a letter to her cousins Lucy and Pierre LeBrun. Included in the same envelope is a letter from Avery Morgan, Julia's brother, to the cousins dated November 15th, 1898. Julia writes that her brother, Avery, had arrived in Paris very early in the morning. She updates them on her Beaux Arts examination process and her will to keep trying. Her and Avery completed a trip outside of Paris to Amiens, Arras and Rouen. She comments on much of the architecture and other sights they saw. She notes that Avery has not been well since he arrived and that he says she has changed. She ends the letter with pleasantries. In the letter Avery Morgan wrote to Lucy and Pierre Lebrun, he thanks them for a 'hearty send off' and recounts his voyage across the Atlantic Ocean from Hoboken, NJ to Boulogne, France and then early morning train trip to their apartment in Paris. He compares all of the churches they have visited since he has arrived and describes some of their trip. He mentions the loss of the SS Mohegan steamer and mentions that he is pleased a family he met on his voyage over were safe.